Pengetahuan dengan Perilaku Merokok Remaja - Hermin Husaeni; Maria Kurni Menga (Sarana Ilmu Indonesia (salnesia), 2019)
Cigarettes was one of the industrial products and international commodities that contain around 1,500 chemicals harmful to human health, but the behavior of some Indonesian teenagers had assumed that smoking is an inevitable need, a need to get along, a need to relax or share other reasons which makes smoking a normal thing. This study aimed to know the relationship between adolescent knowledge about smoking with smoking behavior in adolescents. Type of research used in this study was descriptive correlational. The number of samples used by 45 respondents. Data analysis used univariate and bivariate gang analysis using the chi-quare test. The result showed that most of the adolescents have high knowledge about smoking namely 15 people (33.3%) of respondents, with the smoking behavior of adolescents showing that the majority of adolescents amounted to 34 people (75.6%) respondents, the relationship of knowledge with adolescent smoking behavior shows that adolescents who have high knowledge with smoking behavior are 34 people (75.6%) respondents. Chi square test results show there is a relationship between knowledge and smoking behavior of adolescents, so that the value of p = 0.002 (p> 0.05). Adolescents with high knowledge experience smoking behavior more than adolescents who lack knowledge about smoking behavior. It expected that the results of this study would be one of the sources of information for the local health office and health center in overcoming disease problems arising from smoking with adolescent smoking behavior. This is valuable information for conducting or determining adolescent smoking behavioral habits.